2019
DOI: 10.1109/access.2019.2904630
|View full text |Cite
|
Sign up to set email alerts
|

Online Evolving Interval Type-2 Intuitionistic Fuzzy LSTM-Neural Networks for Regression Problems

Abstract: Since the existence of fuzziness in the real world, uncertainty could be always present in the reasoning results. Therefore, how to tackle with the hesitation existing in the process of reasoning is a meaningful issue for the construction of the inference system. In this paper, a novel interval type-2 intuitionistic fuzzy neural network based on long-short term mechanism is proposed (LSTM-IT2IFNN). By means of interval type-2 intuitionistic set, the hesitation of reasoning is described and involved to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Experimental results reveal that EKF-based learning models perform better than the GD-based in terms of prediction accuracy. In [11], a hybrid model of GD back-propagation and DEKF is employed for the adjustment of the parameters of IT2IFLS and the model applied to system identification problem.Recently also, Yuan and Luo [12] proposed an online evolving interval type-2 intuitionistic fuzzy LSTM-Neural Networks (eIT2IF-LSTMNN). In [12] and [13], the parameters of the models are optimized using GD-back-propagationand applied for regression problems.Other studies on IT2IFS is the one reported in [14], where arithmetic operations are defined for IT2IFS using generalized trapezoidal type-2 intuitionistic fuzzy numbers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results reveal that EKF-based learning models perform better than the GD-based in terms of prediction accuracy. In [11], a hybrid model of GD back-propagation and DEKF is employed for the adjustment of the parameters of IT2IFLS and the model applied to system identification problem.Recently also, Yuan and Luo [12] proposed an online evolving interval type-2 intuitionistic fuzzy LSTM-Neural Networks (eIT2IF-LSTMNN). In [12] and [13], the parameters of the models are optimized using GD-back-propagationand applied for regression problems.Other studies on IT2IFS is the one reported in [14], where arithmetic operations are defined for IT2IFS using generalized trapezoidal type-2 intuitionistic fuzzy numbers.…”
Section: Related Workmentioning
confidence: 99%
“…The test signal in (34) is adopted to test the quality of prediction. Similar to [12], we adopt the same training data and time steps as in system identification 1. To reduce the complexity of the system, two inputs u(t) andy(t)are passed into the IT2IFLS.…”
Section: System Identification Problemmentioning
confidence: 99%
“…These present IT2IFS as a different architecture from IVIFS. The interval type-2 intuitionistic fuzzy logic systems (IT2IFLSs) have found applications in many problem domains such as time series (Eyoh et al, 2017, Luo et al, 2019, regression problems (Eyoh et al, 2018a, Yuan andChao, 2019) and identification and prediction problems (Eyoh et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the IFS of type-1 is designed around a single point of view and may not capture various forms of uncertainties, Eyoh et al [31] presented a rule-based interval type-2 intuitionistic fuzzy logic system (IT2IFLS) that are defined using fuzzy MFs and NMFs together with hesitation indexes. The IT2IFLS has successfully been applied to solve many applications in different domains with impressive performance such as load forecasting [35], time series prediction [36], [37], [38], [39], [40], [41], identification and prediction problems [31], [42], [43], regression problems [44], [45] transportation problems [46] and many more. To the best knowledge of the authors, this is the first study that adopts IT2IFLS with MF, NMF and hesitation indices for software fault prediction.…”
Section: Introductionmentioning
confidence: 99%